Synthesis and Testing of Graphene/Cuprous Oxide Composite Based Nano Fluids for Engine-Coolants. (2015) - Qadri, Mohammed Zaffersha; Chandran, R. Rama; Ravindra, S.; Velmurugan, V.
Abstract: Graphene/Cuprous oxide nanocomposite was prepared by chemically reduction method with different ratios of GO in Cu2 O. In this method, Graphite oxide was used as precursor of graphene, XRD, FT-IR, SEM analysis were done to know the structure and morphology of the as prepared samples. The nano fluids were prepared by two step process. The as prepared nanocomposites were dispersed into the basefluids like water and Ethylene glycol(1:3 ratio), in different concentrations of composite, with different weight percentages (0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5% and 0.6%) of the nanocomposite for each ratio of the basefluid, the boiling points were measured using ASTM standards. The thermal conductivity was measured for different nano fluids with different temperature using KD2 pro instrument.